Perkembangan Kota Bengkalis Era Reformasi (1998-2020) - Rona Cahyati Simanulang; Bunari Bunari; Asril Asril (CHRONOLOGIA, 2023)
Bengkalis City is located on Bengkalis Island, which is the capital of Bengkalis Regency in Riau Province, where most of its administrative area is on the island of Sumatra. In this regard, Bengkalis City is always crowded with people from the island of Sumatra for government affairs, both government agency permits and other legal documents. The purpose of this study is: (1) to find out how the condition of Bengkalis City was at the beginning of the reform. (2) To find out how the social, economic, and educational conditions of Bengkalis City were from 1998–2020. (3) To find out the driving and inhibiting factors for the development of Bengkalis City in 1998–2020. This research is historical. Data were collected through archive study methods, interviews, and documentation. Data analysis techniques use four components of analysis: data compilation, data classification, data processing, and analyzing and interpreting the results. The result of this research is the beginning of reform. Bengkalis District is still lagging. However, after the 1999 Regional Autonomy Law was enacted to manage their households, Bengkalis City began to develop, and the population of Bengkalis City continued to grow from 1998 to 2020. The construction of three ports (domestic and international) could both boost the economy and become an impediment because these ports were the exit points for entry into the City of Bengkalis.